A PATIENT DENGUE HEMORRHAGIC FEVER WITH SPASMS - Kholili, Ulfa; Nasronudin, Nasronudin (Institute of Topical Disease, 2014)
Indonesia is one of the countries with the high endemic of Dengue viral infection followed by Thailand, Myanmar, India and Srilanka. For more 10-15 years, Dengue Viral Infection/DHF has become a cause of patient who should be hospitalized and was the first cause of death children in south easthern Asia.1,2 Batavia was the first city of Indonesia found Dengue Viral infection which had been written in journal by David Bylon in the 1779. Encephalopathy of dengue (ED) is one unusually complication of dengue viral infection which had been characterized by aberration the arrangement of nerves central (CNS). This paper want to describe of a young teenage with suffer from DHF and seizure. Beside it, pleural effusion and cerebral edema had been found. Seizure most likely due to dengue encephalopathy associated with cerebral edema and was supported by positive IgG and IgM anti dengue. Corticosteroid was given toimprove cerebral edema. By good management as long as admission, she was discharged from hospital with a good condition.